Analysis of wireless connectivity applications at airport surface - Ayub, Shahid; Petrunin, Ivan; Tsourdos, Antonios; Xu, Zhengjia (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The main objective of the current work is to carry out the research to explore the potential wireless communication technologies that can be used during a flight operation at the airport surface for current and potential data applications in future. An important part of this work is the analysis of these services and applications from the perspective of understanding the stakeholders and communication means involved. Different communication services including both critical and non-critical ones are analyzed for aircrafts, airlines, and airport connectivity covering flight stages from landing at the airport to taking off from the airport. We are also proposing the ways of more effective use of communication means including the proposed measures for throughput improvement in order to better meet the needs of the airport stakeholders
Keywords: Load balancing; Network performance; Situational awareness of airline operations; In- Flight Entertainment; Datalink systems; Airport connectivity